Air gasification of high-ash solid waste in a pilot-scale downdraft gasifier: Experimental and numerical analysis. (1st May 2023) - Vikram, Shruti; Deore, Sujeetkumar P.; De Blasio, Cataldo; Mahajani, Sanjay M.; Kumar, Sandeep
Abstract: The present work investigates the effect of process parameters on the gasification potential of high-ash solid wastes in a downdraft gasifier using experimental and simulation studies. The air gasification of lignocellulosic garden waste was conducted in a lab-scale fixed bed reactor for the equivalence ratio range of 0.25–0.39. An exhaustive model was devised in Aspen Plus process simulator incorporating the parametric geometry of the gasifier and comprehensive gasification kinetics. Furthermore, the developed model was validated using the experimental results and a fair agreement was obtained. Both the experimental and simulation studies affirmed that the maximum gasification efficiency was obtained at an equivalence ratio of around 0.32. Sensitivity analysis was conducted to scrutinize the effect of critical process parameters on output parameters such as producer gas composition, lower heating value, carbon conversion efficiency, and system's cold gas efficiency. This modeling approach provides valuable insight for generating producer gas from low-grade biomass by optimizing the operating parameters of the downdraft gasifiers. This research can also assist as a guide for stakeholders in renewable energy, waste to energy, and environmentally friendly technologies. Graphical abstract: Image 1 Highlights: Experiments and modeling investigation of downdraft gasification of high-ash solid wastes. Validation of reaction kinetic model with experimental data for different equivalence ratios. Model applications and process optimization under varying operating conditions. High-ash feedstock application in waste reduction and renewable fuel generation.